Thermal reliability of copper alloy–diamond composites produced by field-assisted sintering technology. (April 2016) - Rape, A; Kulkarni, A; Bhat, B; Singh, J
This paper highlights the thermal properties of copper–diamond composites fabricated by field assisted sintering technology. The samples were fabricated using a matrix of copper alloyed with silver and zirconium. Previous reports have shown that these samples possess high thermal conductivity. This work examines the thermal conductivity of the samples after being subjected to thermal cycling. Coefficient of thermal expansion is also reported in this work.